Sistem Informasi Stok Barang Pada PT. Megah Mas Prima Berbasis Web - Haryanto Haryanto; Sendy Zul Friandi; Della Nurfadilla (UNIVERSITAS RAHARJA, 2021)
PT. Megah Mas Prima is a privately owned company that produces accessories and raw materials for the production of shoes. With the large number of items that have been produced and stored in the warehouse, the warehouse section is routinely recorded every day so that the number of items stored in the warehouse can be recorded properly. The problems faced by PT. Megah Mas Prima is using table data in the form of excel and recorded by the warehouse admin. However, this raises a problem such as the amount of raw materials or stock of goods in the warehouse with excel data which is often inappropriate. In fact, the warehouse admin is always wrong in calculating the amount of available stock. And if the computer device is damaged, the file will be lost. PT. Megah Mas Prima requires a website-based design to make it easier for admins to input available items. The purpose of this research is to facilitate the calculation of stock data on goods stored in warehouses by using an effective and efficient system. To make the system design work according to the company's needs, several tools are used, including UML diagrams such as use case diagrams, activity diagrams and sequence diagrams. So that using the website-based system will run according to the needs of the company for calculating the stock of goods available in the warehouse.